Peningkatan Pemahaman Kesiapan Kerja Calon Lulusan UNDANA Melalui Penyuluhan Tes Potensi Akademik - Irna Karlina Sensiana Blegur (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The purpose of this Community Service (PkM) activity is to increase the understanding of graduate candidates of Nusa Cendana University (Undana) regarding the importance of preparing for the Academic Potential Test (TPA) as part of job search readiness. The PkM team from the Mathematics Education Study Program, collaborated with the head of the Center for Information Services, Job Opportunities and Career Development (LIKKPK), Institute for Research and Community Service (LP2M) Undana so that there were one hundred and thirty-five graduate candidates who were actively involved. This activity was carried out through the preparation and implementation stages. During the preparatory stage, the PkM Team prepared TPA materials based on request by the LP2M Team. For the implementation phase, activities were carried out classically three times outside the network in August and September. Discussion, question-answer, practice are the methods used. There were 3 sub-topics discussed at each meeting: 1) Definition and function of TPA, 2) Types and examples of TPA questions, 3) TPA success tips. The results of the evaluation showed that this counseling had succeeded in achieving the stated objectives. This is indicated by most counseling participants who gave a positive response through the open questionnaire given.